2021
DOI: 10.1149/2162-8777/ac12b6
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Parylene-Based Adhesive Bonding Technology for 150 and 200 mm Wafers for Fully Biocompatible and Highly Reliable Microsystems

Abstract: Wafer bonding is a crucial process for fabricating microsystems. Within this study, the polymer parylene was used to establish a low-temperature adhesive wafer bonding process for wafers of 150 and 200 mm diameters. The bonding process was investigated for silicon and glass wafers with different additional coatings including silicon dioxide, silicon nitride, aluminum, and parylene C. Important process parameters such as bonding temperature and time were also investigated and the parylene adhesive was analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…The non-patterned waferwafer bonding is prone to external local defects. These results are similar to results reported earlier by other groups [21,24] The mechanical strength of the parylene-parylene bond interface was investigated by determining the tensile and shear strength using a universal test machine (H5K5, Tinius Olsen), as shown in figures 7(c) and (d). Both sides of the bonded wafer were glued to a wooden specimen using Araldite epoxy resin.…”
Section: Parylene-parylene Bondingsupporting
confidence: 86%
See 1 more Smart Citation
“…The non-patterned waferwafer bonding is prone to external local defects. These results are similar to results reported earlier by other groups [21,24] The mechanical strength of the parylene-parylene bond interface was investigated by determining the tensile and shear strength using a universal test machine (H5K5, Tinius Olsen), as shown in figures 7(c) and (d). Both sides of the bonded wafer were glued to a wooden specimen using Araldite epoxy resin.…”
Section: Parylene-parylene Bondingsupporting
confidence: 86%
“…An alternate process may be envisaged where the recrystallization may be done during bonding itself instead of prior to the bonding. Prior work [21] on the parylene-parylene utilized bonding at 260 • C for a near-hermetic bond. To compare our method with the previously reported results, paryleneparylene bonding done at 260 • C was used as the alternative.…”
Section: Recrystallization Of the Parylenementioning
confidence: 99%
“…50−52 In addition, parylene C can be produced as uniform films with thicknesses in the submicrometer range by room-temperature chemical vapor deposition. 53,54 Silicon is a typical material in MEMS/NEMS processes due to its toughness and reliability 55 and has a Young's modulus of 169 GPa. 56 In addition, silicon oxide, polysilicon, and silicon nitride can be fabricated more uniformly than polymeric materials.…”
Section: Membrane-based Mems/nems Biosensors Based On Static Mode Tra...mentioning
confidence: 99%
“…Parylene in general is primarily used as a sealing coating since it has great barrier properties. There are a lot of research papers to be found on parylene C, which is also the most used parylene type in the electronics industry [9][10][11][12][13][14][15][16]. On the other hand, a much lower number of papers are to be found on the parylene type AF4 (aliphatic fluorinate-4), which, especially in comparison to the other parylene types, stands out due to its high thermal stability (up to 550 • C) [17].…”
Section: Introductionmentioning
confidence: 99%